Softness Parameter and the Energy Ratios for Deformed Nuclei - Baker, Jalal Hasan (Advances in Social Sciences Research Journal, 2017)
In this article the softness parameter is calculated for the chosen nuclei Using the NS2 model. The energies are calculated from NS2 model, and AB model. The experimental energy ratios (R4) and predicted energy ratios from NS2 model are calculated. The predicted values of energies and energy ratios are compared with experimental data.